Pre-treatment of sago fibre for maximum fermentable sugars production - Ugam, anak Janggu (Universiti Malaysia Sarawak (UNIMAS), 2012)
~Sago hampas or sago fibre derived from sago effluent was subjected to pre-treatment for production of fermentable sugars and further fermented to ethanol. Pre-treatment of sago fibre was important to increase fibre susceptibility toward enzymatic hydrolysis. In the study on pre-treatment, different pre-treatments were investigated; steaming, alkaline boiling followed by suspending in diluted acid (acid suspending) and alkaline boiling followed by boiling in diluted acid (acid boiling} The study revealed that steaming pre-treatment gave high lignin reduction (49.2%) and significant cellulose convertibility (41.99 ± 8.12%), suggesting that steaming as the best pre-treatment along with absence of chemical deployment which is crucial for further enzymatic hydrolysis. Studies on steaming optimization displayed the high cellulose recovery (39.63 ± 9.23%), hydrolyzed reducing sugars (36.85 ± 0.95 giL) and starch content (12.28 ± 0.19 giL) achieved at fibre concentration of 7.5%, while boiling at 45 minutes exhibit comparable performance as steaming, which provide more economic solution. In the study on enzymatic hydrolysis, steamed sago fibre (- 40% cellulose) was hydrolyzed using cellulase (NS50013) and pglucosidase (NS500 1 0, Novozyme) and the best concentration after 12 hours was demonstrated at 20% and 0.5% (v/w), respectively. Optimal parameters in enzymatic hydrolysis of sago fibre to fermentable sugars were investigated. In optimal pH determination, pH 4.5 depicted the highest reducing sugars yield (3.98 ± 0.04 gIL) with high saccharification percentage (19.63 ± 0.2%) compared to pH 5 (18.78 ± 0.51%), pH 5.5 (13 .03 ± 1.08%), pH 6 (5.77 ± 1.3%) and pH 6.5 (0.36 ± 0.44%). High reducing sugars yield (8.86 ± 0.12 giL) obtained contributed to high saccharification (43.71 ± 0.6%) as exhibited at hydrolysis temperature of 45°C compared with temperatures at 50°C, 55°C, 60°C, 65°C and 70°C. In the study on the different buffers for hydrolysis, distilled water used as buffer showed the best perfonnance at high reducing sugars yield (10.96 ± 0.46 giL) and percentage of saccharification (54.05 ± 2.28%), comparable with well studied buffers, for example, odium acetate and sodium citrate buffer, at 52.19 ± 3.66% and 55.90 ± 4.91 %, respectively. For maximal hydrolysis, different sago fibre concentrations were studied. The accharification increased with substrate concentrations until it reached 6% (w/v) and here the substrate concentrations showed lower saccharification and reducing sugars yield obtained, suggesting the highest yield can be obtained at 6% (w/v). Studies on the supplementation of enzyme complex (NS50012, Novozyme) revealed that further substrates (cellulose and cellobiose) inhibition were eliminated as evident by optimum saccharification (49.12 ± 1.05%) obtained at enzyme concentration of 0.1% (w/v %). In the study on fermentability of SFS in different buffers (acetate buffer and distilled water) and different yeast strains (Saccharomyces cerevisiae CSIOI and commercial baker's yeast), comparable fennentation efficiency utilizing both buffers was achieved, for example, acetate buffer at 87.76% and distilled water at 87.31 %. Commercial baker's yeast was chosen as the best fermenting microorganism due to the low cost and availability with high ethanol yield (45 .26%) compared to S. cerevisiae CSI-OI (44.53%).